Novel multicomponent organic–inorganic WPI/gelatin/CaP hydrogel composites for bone tissue engineering. Issue 11 (22nd July 2019) - Dziadek, Michal; Kudlackova, Radmila; Zima, Aneta; Slosarczyk, Anna; Ziabka, Magdalena; Jelen, Piotr; Shkarina, Svetlana; Cecilia, Angelica; Zuber, Marcus; Baumbach, Tilo; Surmeneva, Maria A.; Surmenev, Roman A.; et al.
Abstract: The present work focuses on the development of novel multicomponent organic–inorganic hydrogel composites for bone tissue engineering. For the first time, combination of the organic components commonly used in food industry, namely whey protein isolate (WPI) and gelatin from bovine skin, as well as inorganic material commonly used as a major component of hydraulic bone cements, namely α‐TCP in various concentrations (0–70 wt%) was proposed. The results showed that α‐TCP underwent incomplete transformation to calcium‐deficient hydroxyapatite (CDHA) during preparation process of the hydrogels. Microcomputer tomography showed inhomogeneous distribution of the calcium phosphate (CaP) phase in the resulting composites. Nevertheless, hydrogels containing 30–70 wt% α‐TCP showed significantly improved mechanical properties. The values of Young's modulus and the stresses corresponding to compression of a sample by 50% increased almost linearly with increasing concentration of ceramic phase. Incomplete transformation of α‐TCP to CDHA during preparation process of composites provides them high reactivity in simulated body fluid during 14‐day incubation. Preliminary in vitro studies revealed that the WPI/gelatin/CaP composite hydrogels support the adhesion, spreading, and proliferation of human osteoblast‐like MG‐63 cells. The WPI/gelatin/CaP composite hydrogels obtained in this work showed great potential for the use in bone tissue engineering and regenerative medicine applications.